Balanced Scorecard Analysis To Assess The Performance Of Tirta Hidayah Regional Public Company (Perumda), Bengkulu City - bima tri abiyyu; Erwin Febriansyah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Measuring company performance is important in a company, both government and private agencies, because by measuring performance it can be seen the effectiveness of strategy determination and its implementation. The aim of the research is to analyze and describe the performance of Perumda Tirta Hidayah Bengkulu City by using the balanced scorecard method.This research was conducted at the office of Perumda Tirta Hidayah Hibrida Street 15 No. 81 Sidomulyo Village, Gading Cempaka District, Bengkulu City. The research instrument uses the Balanced Scorecard developed by BPPSPAM (2013), namely financial aspects, operational aspects, service aspects and HR aspects in 2021-2022. Data collection through documentation, observation and literature study and data analysis using quantitative descriptive analysis method.The results of the study revealed that the performance of Perumda Tirta Hidayah Bengkulu City using the balanced scorecard method in 2022 was in the healthy category (3.33) and in 2021 in the healthy category (3.17). The financial aspect with three indicators (cash ratio, collection effectiveness and solvency) has good performance, and two indicators (ROE and operating ratios) have poor performance. The service aspect with three indicators (technical service coverage, complaint settlement rate and customer water quality) has good performance, and two indicators (subscriber growth and domestic water consumption) have poor performance. The operational aspect has three indicators (production efficiency, service operating hours and customer water pressure) performing well, and two indicators (water loss rate and water meter replacement) performing poorly. The HR aspect with two indicators (the ratio of the number of employees and the training and education staff ratio) performs well, and one indicator (training costs to personnel costs) performs poorly. Keywords : Balanced Scorecard, Company Performance, Perumda Tirta Hidayah